2007
DOI: 10.1177/112070000701700102
|View full text |Cite
|
Sign up to set email alerts
|

A Lateral Minimal-Incision Technique in Total Hip Replacement: A Prospective, Randomized, Controlled Trial

Abstract: Minimally invasive surgery has become a trend over the last few years in all aspects of orthopaedic surgery, including total hip arthroplasty. So-called mini-incision techniques involve limiting the length of the skin incision to 10 cm with use of either an anterior, lateral or posterior approach. Between March 2004 and December 2005 one hundred consecutive unilateral total hip replacements were performed by the same senior surgeon in our institute. All patients were randomly assigned to study group (group A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Two high-quality studies and five medium-quality studies reported a moderate to large decrease in operative time for MIS THA [23,27,30,32-34,37]. One other high-quality study and eight medium-quality studies reported no significant difference in operative time [4,17,24-26,28,29,35,36]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two high-quality studies and five medium-quality studies reported a moderate to large decrease in operative time for MIS THA [23,27,30,32-34,37]. One other high-quality study and eight medium-quality studies reported no significant difference in operative time [4,17,24-26,28,29,35,36]. …”
Section: Resultsmentioning
confidence: 99%
“…Two high-quality studies [4,34] and eight medium-quality studies [23,25-27,29,33,36,37] reported a small-to-large decrease in intraoperative blood loss after MIS THA. One high-quality study and three medium-quality studies reported no significant difference [24,30,32,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lack of consensus over the actual definition of MIS and the relationship between skin incision and soft tissue trauma. Speranza et al [32] and Procyk [33] suggested that the ideal MIS is that of a procedure which has little tissue disruption without cutting muscles and tendons and therefore less pain to provide a significantly shorter rehabilitation with longer-term outcomes which are equal or better to a conventional approach. Accordingly, the little difference in outcomes reported in this metaanalysis may be attributed to similarities in the operative procedure after the skin incision for traditional and MIS procedures.…”
Section: Discussionmentioning
confidence: 99%